First assessment of the impact of the new countries accession - especially Cyprus & Malta - to EU - Γουλιέλμος Αλέξανδρος Μ. (SPOUDAI Journal of Economics and Business, 2005)
This paper deals first with the so-called wealth gap between EU-15 and CC-13, which is an important handicap that EU cohesion policy gives the lion's share and its primary attention. Concern is also expressed for the regional development and integration of regions and countries. New trade theory is mentioned and recommended for all CC-13 and for Cyprus and Malta. The disadvantages for and the advantages of accession are mentioned next. Specific reference to Cyprus and Malta is next attempted. Cyprus must become more a new City of London providing maritime services to Balkan group and Turkey. The know-how has to be bought not invited through FDI. In Maritime matters Cyprus is strong with 36 m dwt and behind Malta with 40m dwt. Cyprus had made substantial pre-accession progress and improved MOU performance. Malta had better MOU performance in 2003. But progress must be made under the chapter of the adoption of certain key international conventions like Marpol. JEL Classifications: F15, L49